Pacing to prevent atrial fibrillation. (January 2017) - Chutani, Surendra K.; Shah, Arti N.; Kantharia, Bharat K.
Abstract : Purpose of review: Pacemakers are frequently implanted in patients with atrial fibrillation. Many patients with pacemakers also develop atrial fibrillation. Over a period of time, through many studies on different pacing modes, sites, and algorithms, significant insights have been gained in the field of treatment and prevention of atrial fibrillation. The purpose of this review is to discuss some aspects of the scientific basis, current standards and possible future research related to cardiac pacing for prevention of atrial fibrillation. Recent findings: Trials involving pacing at the alternative pacing site per se or in combination with specific algorithms for prevention of atrial fibrillation have not shown consistent results. Recently, a new generation of antitachycardia pacing therapies has brought on a new optimism with promising outcome data of reduction in permanent atrial fibrillation, cardiovascular hospitalizations, and mortality. Summary: Multiple trials and clinical observational studies of different pacing methods and algorithms, with the exception of newer therapies in conjunction with atrial pacing algorithms, have not been shown to prevent atrial fibrillation. Hence, while permanent pacing is indicated for sinus node dysfunction and conduction abnormalities in patients with or without atrial fibrillation, the prevailing data in the literature does not support implantation of a permanent pacemaker for prevention of atrial fibrillation per se.